STRATEGI PENINGKATAN DAYA SAING LEMBAGA PENDIDIKAN: STUDI PERUMUSAN DI SMKN 1 BENDO MAGETAN - Muhammad Khoirul Anam (Al-Mabsut: Jurnal Studi Islam dan Sosial, 2025)
This research is motivated by the increasingly tight competition between educational institutions that demands the existence of appropriate management strategies to increase competitiveness, especially in SMKN 1 Bendo Magetan as a leading school. The purpose of this study is to describe the formulation of management strategies in the formulation of competitiveness of educational institutions at SMKN 1 Bendo Magetan. In this paper using a qualitative approach with data collection techniques carried out through observation, in-depth interviews, and documentation, with research subjects including the principal, vice principal, educators, and other related parties. Data analysis was carried out descriptively qualitatively through the stages of data reduction, data presentation, and drawing conclusions. The results of the study indicate that the strategy to increase competitiveness at SMKN 1 Bendo Magetan is guided by the vision and mission of the institution with an emphasis on improving the quality of human resources, strengthening cooperation with the industrial world and universities, developing extracurricular programs and student character, and adjusting the curriculum to industrial needs through the teaching factory program. In addition, the active involvement of all stakeholders and long-term oriented strategic planning are important factors in supporting the success of this strategy, so that the quality of graduates increases to become competent individuals, with superior character, and ready to face competition in the work environment and further education. Keywords: strategy formulation, competitiveness of educational institutions, strategic management.